Harry Potter and the goblet of fire (Calif : Warner Home Video, 2006)
Harry's fourth year at Hogwarts is marked by the Quidditch World Cup and the Triwizard Tournament, in which student representatives from three different wizarding schools compete in a series of increasingly challenging contests. However, Voldemort's Death Eaters are gaining strength and create the Dark Mark - giving evidence that the Dark Lord is ready to rise again. In the unsuspecting lives of the students at Hogwarts, the competitors are selected by the goblet of fire, which this year makes a very surprising announcement: Hogwarts will have two representatives in the tournament, including Harry. Now Harry has to rise to the challenge for the Tri Wizard Tournament while keeping up with school.